2023
DOI: 10.3390/biology12060842
|View full text |Cite
|
Sign up to set email alerts
|

Myosin Heavy-Chain Messenger Ribonucleic Acid (mRNA) Expression and Fibre Cross-Sectional Area in Masseter, Digastric, Gastrocnemius and Soleus Muscles of Young and Adult Rats

Abstract: Different demands on the muscles of mastication may influence their functional profile (size and distribution of muscle fibre types), which may change during growth and maturation, potentially influencing craniofacial growth. The aim of this study was to evaluate mRNA expression and cross-sectional area of masticatory muscle fibres compared with limb muscles in young and adult rats. Twenty-four rats were sacrificed at two different ages, namely 12 at 4 weeks (young) and 12 at 26 weeks (adult). The masseter, di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…These 2 genes are associated with skeletal muscle function. 21 , 22 Both Actn3 and Myh4 have been shown to be expressed in high levels in skeletal muscle cells, a tissue not to be expected to be present in calvaria bone preparations. Yet, our pathway analyses showed that the genes differentially regulated in male mice samples were mostly associated with muscle function, suggesting that they might also be expressed in bone cells and, in particular, in osteocytes.…”
Section: Discussionmentioning
confidence: 99%
“…These 2 genes are associated with skeletal muscle function. 21 , 22 Both Actn3 and Myh4 have been shown to be expressed in high levels in skeletal muscle cells, a tissue not to be expected to be present in calvaria bone preparations. Yet, our pathway analyses showed that the genes differentially regulated in male mice samples were mostly associated with muscle function, suggesting that they might also be expressed in bone cells and, in particular, in osteocytes.…”
Section: Discussionmentioning
confidence: 99%